PEMBANGUNAN SIRKUIT MANDALIKA BERDAMPAK TERHADAP PENINGKATAN PENDAPATAN UMKM DI DESA SADE LOMBOK TENGAH - Risma Sahrani Putri; Jihan Syaharani; Buanita Berliana Putri (Nusantara Hasana Journal, 2023)
This study aims to determine the effect of the construction of a MotoGP circuit in the village of Sade, Central Lombok. This type of research uses qualitative methods, the population in the study is the surroundings in Sade Village, Central Lombok. Sade is a village located in the south of Central Lombok, this village is quite well known in international circles, because of its culture and customs, what is best known in the international arena in Dase is its traditional house, because the traditional house is still classified as traditional, and far from being luxurious, even though in modern times, this village still maintains its customs and ethics. Because it is well-known internationally, the majority of jobs in this village are woven cloth traders and farmers.